The first book of swamps and marshes - Smith, Frances C., 1901- (New York : Franklin Watts, 1969)
A discussion of various types of swamps and marshes, their economic importance, the need to conserve and manage them, and the plant and animal life inhabiting them
Keywords: Wetland ecology -- Juvenile literature; Wetland conservation -- Juvenile literature